ASSESSING THE IMPACT OF TALENT MANAGEMENT PRACTICES ON THE REPUTATION OF MEDICAL LABORATORIES IN BENGHAZI, LIBYA - Alferjany, Muhammad Abdullah Omar Ali; Younis, Adel Rabeh (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2025)
This research investigates how talent management (TM) practices influence the reputation of medical laboratories in Benghazi, Libya. The study utilized a custom-designed questionnaire comprising 52 items based on a five-point Likert scale. Employing a descriptive-analytical method and multiple regression analysis, the research gathered responses from a stratified random sample of 255 participants, achieving a 90.16% response rate. The results indicate a strong application of both talent management and organizational reputation variables. A significant positive impact of TM on organizational reputation was observed (β = 0.720). Based on these findings, the study recommends enhancing talent management strategies, including developing structured plans for attracting and retaining skilled professionals, fostering innovation, and ensuring the availability of modern technologies to strengthen service quality and institutional reputation.